Ewolucja koncepcji „szczególności Arktyki” w kontekście wpływu wojny rosyjsko-ukraińskiej na sytuację międzynarodową na Dalekiej Północy (luty–grudzień 2022) - Damski, Przemysław Piotr (Forms of Power in Contemporary World – Case Studies, 2023)
For thirty years since the end of the Cold War, the Arctic, and the international regime there have been characterised as “exceptional”. However, there have been many definitions of “Arctic exceptionalism” and it is difficult to identify one to which all states in the region subscribe. At the same time, the concept was changing over time and adapting to new conditions, right up to the Russian aggression against Ukraine on 24 February 2022. Crucial to this was the policy of Russia and the United States, the only global powers that are Arctic states which, until the war in Ukraine, respected the norms and principles developed for the Arctic based on trust. The aggression against Ukraine undermined Russia’s credibility and highlighted how divergently the various Arctic players understood “exceptionalism”. As a result, Western states began to rally around the US and isolate Russia by depriving her, at least for a time, of her “territory of negotiations”. In response, they were met with military demonstrations designed to induce them to return to the status quo ante bellum. However, this has not been successful, has led to a strengthening of the US position in the region and has cast doubt on the continuation of the “exceptionalism” in its current form.